Effects of different hot pressing processes and NFC/GO/CNT composite proportions on the performance of conductive membranes. (15th January 2021) - Zou, Haojie; Li, Xinpu; Zhang, Yuanqiao; Wang, Zining; Zhuo, Bing; Ti, Pu; Yuan, Quanping
Abstract: In this study, both nanofibrillated cellulose (NFC) and graphene oxide (GO) as dispersant and binder, were employed to effectively disperse and assemble carbon nanotube (CNT) via ultrasonic dispersion. A NFC/rGO (reduced graphene oxide)/CNT conductive composite membrane was prepared via a low-temperature and efficient hot pressing treatment with the synergistic effect of drying, reduction, and densification, which exhibited good conductivity, mechanical performance, and thermal stability. After the composite membrane (mass ratio of NFC:GO:CNT was 2:4:4) was hot pressed under 3 MPa at 170 °C for 30 min, its sheet resistance reduction rate reached to 61.1% (decreased from 19.8 ± 3.1 Ω sq. −1 to 7.7 ± 1.1 Ω sq. −1 ), while its Young's modulus increased from 1496.3 ± 250.9 MPa to 3178.3 ± 356.2 MPa. Hot pressing at the low temperature can reduce oxygen-containing groups on GO, by which the carbon-to‑oxygen ratio was increased from 2.28 to 5.05. The presented controllable method helps to construct a conductive network in the composite membrane, and provides a new strategy to enhance performance of the low-dimensional carbon composite membrane. Graphical abstract: Unlabelled Image Highlights: A stable and flexible NFC/rGO/CNT conductive composite membrane was prepared via a low-temperature hot pressing process. The hot pressing process simultaneously attained the reduction of GO, densification and drying of the composite membranes. Both NFC and GO with good dispersibility were used to synergistically drive the dispersion of CNT. The presented design for the process is efficient and environmentally friendly to the manufacture of the composite membranes.